PENTINGNYA PENDIDIKAN KARAKTER ANAK BANGSA DALAM PENDIDIKAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) (untuk Dosen dan Mahasiswa STMIK Nurdin Hamzah) - Faiza Rini (JURNAL AKADEMIKA)
Now days the development of increasingly sophisticated technology. The emergence of Information Communication Technologies ( ICT ) or in Indonesian called Teknologi Informasi dan Komunikasi (TIK), has affected almost all sectors , including education . Teaching and learning become easier because of the role of ICT . Humans become easier to find the things she wanted to know . In addition to convenience , ICT also has deficiencies that pose a negative impact to human life . Therefore , as an educated man , must be proficient in the use of today's technology . Because if the technology is not used when undue , it will harm himself or others. Once the importance of the role of ICT , also look at the impact that may result from the development of ICT , the use of ICT should remain limited to the things that are only useful. if only technological developments , especially in the world of education can help the implementation of education properly and smoothly . Because if education has been going well , it will come true men of character and self-sufficient . Thus, this nation will be a nation that is also character and independent .